Is there any relationship between hearing threshold levels and CD4 cell count of human immunodeficiency virus infected adults? (2016)
Background: The role of viral load level and/or CD4 (Cluster of differentiation 4) cell count in the aetiopathogenesis of hearing loss in HIV infection is unclear. Therefore, we investigated the relation hip between CD4 cell counts, viral load and hearing threshold of HIV (Human immunodeficiency virus) infected adults. Methods: This cohort audiometric study involved consecutive HIV-infected and HIV-uninfected adults as controls. Clinical data relating to hearing loss, HIV status, and highly active antiretroviral therapy (HAART) were obtained. Audiometric evaluation was performed. The most recent CD4 cell counts and RNA viral load of HIV-infected participants were obtained from clinic records. Results: There were 299(66.7%) HIV-infected adults and 149(33.3%) controls with mean age of 39.64± 12.45 years and 39.60±12.45 years respectively (p=0.98). In both groups, there were more participants with Ieft hearing loss. Mild to profound hearing loss was found in 65.9% H IV infected participants and 53.7% controls. Majority (86.3%) of the HIV-infected participants were on HAART. The mean CD4 cell count was 654.58±289.15 in 41 HIV-infected participant not on HAART and 523.95±300.17 in 258 participants on HAART (p=O.O I). Majority, 197 (62%) HIV infected participants with hearing loss had CD4 cell count S200 cells/mm'. Higher viral load significantly correlated with low CD4 cell counts (p<0.01; r= 0.18) and low CD4 cell count significantly correlated with high hearing threshold (p<0.01; r= 0.17) Conclusion: There was a trend towards more hearing loss among the HIV-infected adults. The higher hearing threshold in those with low CD4 cell counts of <200 cells/mm3 suggests possible relationship between hearing status and severity of HIV disease.